Integrating World Englishes in English-Medium Instruction: A Systematic Literature Review for Inclusive Pedagogy - Hawa, Faiza; Rohmatillah,; Basikin, Basikin; Ciptaningrum, Dyah Setyowati; Wibowo , Adjie Pradana (JOLLT Journal of Languages and Language Teaching, 2026)
The speedy growth of English-Medium instruction (EMI) in higher education has brought more concern on language equity and inclusion. Following the situutation, some challenges concerning on persistent language standard ideology, native-speaker centering, internalization pressure, and and teachers’ lack preparation for multi language classroom existed. This study examined how WE is integrated within EMI and identified an insistent void between theory and classroom practice. While current studies progessively concentrate on inclusive and pluralistic approaches, a study on sustained pedagogical integration and its implication of integrating WE into EMI is lacking. Adopting Systemic Literature Review (SLR), 22 articles issued in the year between 2014-2025 were examined. The results indicate that incorporating World Englishes into English Medium Instruction faces challenges related to idelogogical, institutional, stemming mostly from native-speakerism impact and lack of training support for lecturer. Nonetheless, positive trend is emerging in the acceptance of english variation among teacher and students, especially within intercultural communication setting. The findings bring wider implications for educators and policy makers aiming to connect internationalization objectives with inclusive pedagogies within higher education level like the need for adopting translanguaging strategies, developing context-sensitive curricula, and improving teachers’ intercultural competence. This study underlines that incorporating World English into English Medium Instruction goes beyond language proficiency, fostering more comprehensive, fair, and adaptable learning context in higher education globally.